PENGARUH NIPPLE STIMULATION TERHADAP KEMAJUAN PERSALINAN PADA IBU PRIMIPARA : EVIDENCE BASED CASE REPORT (EBCR) (Jurnal Kesehatan Siliwangi, 2022)
Background: Induction of labor is considered as a method of initiating uterine contractions to achieve cervical effacement and dilation that can lead to vaginal delivery. Nipple stimulation is a natural way that birthing mothers can do to speed up labor progress. This method can be used for induction of labor which allows women to have greater control over the induction process and has the advantage of being effective naturally and inexpensively in the process of application. The use of pharmacological induction has the potential to harm the mother and fetus, because when the frequency of contraction increases, the strength and duration are above normal levels, the circulation of the fetus and placenta can be disrupted resulting in fetal distress. Purpose: To determine whether nipple stimulation take effect in the progress of labor in primipara mother. Method: Research was done using multiple article literature searches, including PubMed and Google Scholar. Result: there is progress on labor during the first stage of labor which is faster in primipara mother after nipple stimulation was performed. Conclusion:This study concludes that there is an effect of nipple stimulation on the progress of labor in primipara mother.